Translating the suffix -ism in linguistics terminology from English into Arabic - Jamal Mohamed Giaber (JoSTrans: The Journal of Specialised Translation)
English relies heavily on suffixation in deriving new words. The suffix -ism is used to form nouns in both general and specialised languages. In linguistics terminology, -ism is used to denote a range of technical concepts. The technical use of -ism and differences in term formation between Arabic and English have some implications for the translation of linguistic terms into Arabic. The aim of this study is to identify the technical senses of -ism in linguistics terminology in English and the translation techniques used by Arab lexicographers in rendering those senses into Arabic. The study findings show that (a) -ism has ten technical senses in linguistics terminology, (b) Arabic has the potential for translating the ten senses either lexically or morphologically, (c) different Arab lexicographers use different translation techniques, most of which produce denotatively acceptable equivalents, but only some techniques produce morphologically concise equivalents, and (d) formal consistency between Arabic equivalents is rarely maintained.